The Influence of Digital Literacy on The Social Behavior of Early Childhood - Nurkhasyanah, Alfiyanti; Ichsan, Ichsan (JOYCED: Journal of Early Childhood Education, 2024)
This study was conducted against the background of children's social behavior which is currently experiencing a decline. Unconsciously, we have now entered a disruptive era where everyone is starting to use the digital world in their daily lives. The predictor that is thought to be able to predict children's social behavior is digital literacy. Therefore, this study tests and analyzes the influence of digital literacy on the social behavior of early childhood. The purpose of this study was to determine the influence of digital literacy on the social behavior of early childhood using this quantitative research method. The researcher studied 20 samples of early childhood in the Pedukuhan Canden, Canden, Jetis, Bantul area. The technique used was a correlation design, then the collected data was analyzed using comparative analysis with the help of SPSS 2.3 For Windows. The conclusion in this study is based on the results of the study, namely the results obtained 0.005 <0.05, it can be said that the data has a relationship between digital literacy and the social behavior of early childhood. With a person value of 0.599 > rtable 0.444, it can be concluded that digital literacy is positively related to the social behavior of early childhood with a sufficient degree of correlation, which means that there is an influence of digital literacy on the social behavior of early childhood in Pedukuhan Canden, Canden, Jetis, Bantul. The implication of the results of this study is the importance of developing digital literacy in early childhood as an effort to improve and enhance their social interactions. With better digital literacy, children are expected to be able to use technology wisely, which not only enriches their knowledge but also improves their social skills. Therefore, it is important for parents, educators, and related parties to provide appropriate learning regarding the use of technology that supports children's social development.